Computed tomography- guided percutaneous core needle biopsy for diagnosis of intathoracic mass lesions: experience at a tertiary care centre of North India - Raghuvanshi, Shivanjali; Bhalla, Shalini; Shahi, Vanshika; Kumar, Manoj; Qayoom, Sumaira; Rawat, Shalini; Srivastava, Anand; Goel, Madhu Mati (International Journal of Research in Medical Sciences, 2019)
Background: CT guided core needle biopsy is a less invasive method for initial diagnostic workup in the assessment of intrathoracic masses. This study was conducted to evaluate the diagnostic yield of the procedure as well as to demonstrate the spectrum of various disease in our population. Methods: Present study was conducted in a tertiary care hospital for a study period of two years. Patients with intrathoracic mass were included and CT guided biopsies were performed following a protocol. The CT guided biopsies received were examined for histological diagnosis. Immunohistochemistry was carried out where ever routine histopathology was not sufficient for diagnosis. Relevant immunohistochemical panels were applied for lung, mediastinal and pleural tumours according to the histological differential diagnosis. Detailed demographic and clinical profiles along with radiological findings were noted. Results: Total of 138 cases were taken for CT guided FNAC procedure and 123 (89.1%) cases yielded diagnostic biopsy. Lung was the most commonly involved organ followed by mediastinum. Bronchogenic carcinoma was the most common lesion reported in lung and Non-Hodgkin Lymphoma was the most common mediastinal lesion. Lung collapse was most common radiological feature. Conclusions: CT guided percutaneous biopsy is a valuable diagnostic technique providing for early accurate diagnosis and being minimally invasive procedure. Care should be taken while tissue processing and section cutting of intrathoracic biopsies as the biopsies are small and tissue loss should be prevented so that sufficient material is available for immunohistochemistry.